Discovery Learning-Based Civics Learning Assisted by Kahoot as an Effort to Improve Critical Thinking in Grade 5 Elementary School Students - Ni Wayan Ari Kusuma Dewi; Dewa Bagus Sanjaya; Nengah Swastika (Thinking Skills and Creativity Journal, 2025)
The low level of critical thinking skills among elementary school students remains a major issue in Civic Education (PKN) learning, particularly due to the dominance of conventional teaching approaches that limit active student engagement. In addition, the use of interactive digital media has not been optimally integrated to support higher-order cognitive processes. This study aims to analyze the effectiveness of Discovery Learning-based PKN instruction assisted by Kahoot in enhancing fifth-grade students’ critical thinking skills. This research employed a pre-experimental design using a One Shot Case Study model. The subjects consisted of 28 fifth-grade students. Data were collected through a critical thinking skills test developed based on established critical thinking indicators. The data were analyzed descriptively using SPSS to obtain the mean score, standard deviation, and the distribution of achievement across indicators. The findings indicate that Discovery Learning integrated with Kahoot promotes active student engagement and facilitates analytical reasoning, inference, and systematic decision-making processes. Conceptually, students’ critical thinking skills were categorized at a high level, with the indicator of providing simple explanations showing the strongest performance, while the strategy and tactics indicator still requires further improvement. The study concludes that the integration of active learning models and interactive digital media has positive implications for developing students’ critical thinking skills. These findings suggest that such instructional approaches are highly relevant for 21st-century Civic Education learning.